SMEs digitalization readiness in supporting Sharia fintech: framework development using quadruple perceives in fuzzy analytical hierarchy process (FUZZY AHP) - Mahyarni, Mahyarni; Okfalisa, Okfalisa (Serbian Journal of Management, 2024)
The role of Quadruple Helix in promoting the development of digitizing SMEs highlights the significant contribution of Sharia fintech as a new challenge to sustainably and creatively face the Covid-19 disruption. This paper developed a framework of SME’s Digitalization Readiness in Supporting Sharia Fintech to scrutinize the quadruple Helix perceptions and the success of digitalization. Furthermore, a Fuzzy-AHP approach is applied to analyze the significant weight of Quadruple Helix interaction and distinguish between universities, industry, communities, and government. This creates the basis of a sustainable corporate sector through the consideration of Information Technology (IT), economy, and Sharia within business activity, transaction, marketing, management, micro- environment, and macro-environment, circumscribed into 24 sub-indicators. This study found that university academicians view business activity as the most significant indication for gauging the digitization readiness of small and medium-sized enterprises (SMEs) based on Sharia fintech. It is followed by marketing, transaction, management, micro, and macro environment. Meanwhile, the other sectors including industry, communities, and government discerned marketing as the deliberation of the SMEs’ Sharia-based success digitalization. This framework stimulates and synergizes an integrated works, innovation, economic growth, productivity, technology, knowledge, and skills of Quadruple Helix roles in facing the competitive advantages of digital era with concerning on the Sharia values. The prioritized analysis and recommendation from this framework admit as a guidance tool for Quadruple Helix in decision making and strategic policies in achieving the success of the digital transformation.